Individual lawyers, the SEC revolving door, and comment letters - SHEN, Michael (Institutional Knowledge at Singapore Management University, 2018)
Government officials, advocacy groups, and the business press have raised concerns that former SEC employees may continue to influence the SEC after leaving the agency. Using a hand-collected database of individual lawyers that represent firms in responding to SEC comment letters, we examine the impact of individual lawyers, and lawyers formerly employed by the SEC, on the comment letter process. We document significant differences between lawyers and law firms in their clients’ resistance to SEC comment letters, and find that firms that retain former SEC employees are larger, more profitable, and more likely to have received a comment letter raising accounting issues. After matching on lawyer, comment letter, and firm characteristics, we find evidence consistent with former SEC employees increasing resistance in the comment letter process: conversations involving former SEC employees involve more negotiation, and result in fewer financial statement amendments.